(untitled) (Castilla. Estudios de Literatura, 2020)
The study tackles the presence of North American cinema in Los dominios del lobo (1971) as a way of rethinking the tradition in Javier Marías’s writing. From this perspective, the article intends to place the novel in its context (the formal and aesthetic revolution of novísimos), considering the break against realism and costumbrism in Hispanic literature during the last years of Franquism. This foreign gaze to Hispanic tradition is visible in the novel by the imitation of forms, styles and North American cinematographic genres. To sum up, the study aims at analyzing the filmic presence of American cinema of Hollywood’s Golden Age in this debut novel, with the purpose of reflecting upon the place of Marías in the hispanic canon.